THE ROLE OF TRANSFORMATIONAL LEADERSHIP ON EMPLOYEES’ INNOVATIVE BEHAVIOUR - Hatamleh, Yazan (Digital Repository of Theses, 2023)
Globalization, competition, communication, and rapid technological development pose enormous challenges to higher education in developing countries. It is evident that innovation allows organizations to be competitive and increase their performance. Many scholars have argued that leadership is an important and crucial factor in achieving employees’ innovative behavior as part of innovation and creativity. A transformational leadership style has been found to have an influence on innovation. This study sought to examine the role of transformational leadership on employees' innovative behavior through the mediation of organizational culture, employee work engagement, and attitude towards change in higher education institutions in Jordan. A quantitative methodological style using a questionnaire survey method approach with close-ended questions. The primary data collection was supported by secondary data vi collected from a comprehensive review of literature and a conceptual framework was created and developed in addition to ten hypotheses. The population consists of academics and administrators from both universities. A total of 420 questionnaires were distributed to both universities. The total number of completed questionnaires returned was 404, resulting a response rate of 96.1%. The quantitative data was analysed by using SPSS 20.0 with AMOS 20.0. The structural model was used to test the hypotheses. The results of the study confirmed that transformational leadership style positively and significantly influences employees’ innovative behavior in Jordanian higher educational institutions. It also confirmed that employees’ work engagement, organizational culture, and attitude toward change play a significant and positive role in the relationship between transformational leadership and employees’ innovative behavior. This study added importance and significant input to the literature in general and the literature of developing countries, including Jordan. Moreover, this study has been tested in the context of higher education, where no other studies have been conducted, which makes this theoretical framework a unique contribution to higher education institutions in general and to developing countries in particular.This study contributes to the literature by enriching the library of theoretical relationships. Also, this study could assist and empower the leaders and policy makers in higher education institutions enhance their innovative behavior.